Non-Hybrid Risk Management: Integration of Sharia Maqashid and Fintech in Risk Mitigation in Sharia Financial Institutions - Sarifah, Sarifatul Aini; Yazid, Muhammad (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
Non-performing financing is one of the main challenges in the Islamic finance industry that can have an impact on the stability and sustainability of Islamic financial institutions (LKS). Unlike the conventional system, LKS is bound to sharia principles, which requires a contract-based risk mitigation mechanism and risk-sharing. This study aims to analyze various approaches to sharia risk management in dealing with non-performing financing through literature study methods. Data was obtained from various scientific literature, regulations, and fatwas related to financing risk management in LKS. The results show that contract-based approaches, such as murabahah, ijarah, musyarakah, and mudharabah, have different levels of risk that require specific mitigation strategies. In addition, the principles of maslahah and ta'awun can be implemented in the form of a fairer and more sustainable financing restructuring. The study also found that a combination of early warning systems, business mentoring, and the use of big data-based technology can increase the effectiveness of sharia risk management. In conclusion, the sharia approach in mitigating problematic financing is not only oriented towards profitability, but also on the balance of justice, protection of customer rights, and Islamic economic stability. This finding is expected to be a reference for regulators and Islamic finance practitioners in formulating more effective risk mitigation policies.